Preliminary structural diagnosis of the Sacsamarca church in Peru using photogrammetry and IR thermography - Briceño Melendez, Carolina (2018)
The application of different diagnostic techniques in a historical construction allows the obtained information to complement each other, which contributes to a detailed and complete data of the conservation state of a building. This paper provides a structural diagnosis of the church “Virgen de la Asunción” of Sacsamarca village in Ayacucho, Peru. Due to exposure to weathering, torrential rains, and past seismic activity, the Sacsamarca church has a poor conservation state. Hence, it is necessary to identify properly the structural pathologies and their extension in the church. A first part of the research was the development of a three-dimensional geometrical model using aerial and terrestrial photogrammetry, aiming to characterize the general damage state of the building, including inaccessible zones. The data generated from the aerial and terrestrial acquisition allowed a detailed identification of the pathologies on the façades. A photographic record was used to detect the anomalies in the interior of the church. Finally, a passive thermography campaign was carried out in order to find additional damage and corroborate the pathologies identified during the visual inspection. The structural diagnosis evidenced that the southern and western wall of the church of Sacsamarca present a high collapse risk, for which emergency actions for their stabilization are recommended.